2003
DOI: 10.1037/0096-1523.29.1.92
|View full text |Cite
|
Sign up to set email alerts
|

The role of response selection for inhibition of task sets in task shifting.

Abstract: Response selection in task shifting was explored using a go/no-go methodology. The no-go signal occurred unpredictably with stimulus onset so that all trials required task preparation but only go trials required response selection. Experiment 1 showed that shift costs were absent after no-go trials, indicating that response processes are crucial for shift costs. In Experiment 2, backward inhibition was absent after no-go trials. Experiments 3 and 4 demonstrated that response selection, rather than execution, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

76
529
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(616 citation statements)
references
References 24 publications
76
529
11
Order By: Relevance
“…Meiran et al (2000) argued that while attention could be redirected to a different dimension 9 during the preparation interval, removing the cost to processing of inappropriate attentional orientation, it is only when the participant actually responds that response-set biasing (changing the meaning of the response set) can be accomplished -hence the residual cost. But more recently, Meiran and colleagues concluded on the basis of simulations of the computational model CARIS (Meiran, Kessler, & Adi-Japha, 2008) that response-set biasing may well occur before stimulus onset, whereas attentional re-setting occurs mainly/only after the stimulus has been presented.A related claim about the importance of making a response was made by Schuch and Koch (2003) on the basis of an observation since replicated and extended in a number of studies (see Los & van der Burg, 2010, for a review). On some trials they presented a 'no-go' signal along with the target stimulus, telling the subject to withhold a response.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Meiran et al (2000) argued that while attention could be redirected to a different dimension 9 during the preparation interval, removing the cost to processing of inappropriate attentional orientation, it is only when the participant actually responds that response-set biasing (changing the meaning of the response set) can be accomplished -hence the residual cost. But more recently, Meiran and colleagues concluded on the basis of simulations of the computational model CARIS (Meiran, Kessler, & Adi-Japha, 2008) that response-set biasing may well occur before stimulus onset, whereas attentional re-setting occurs mainly/only after the stimulus has been presented.A related claim about the importance of making a response was made by Schuch and Koch (2003) on the basis of an observation since replicated and extended in a number of studies (see Los & van der Burg, 2010, for a review). On some trials they presented a 'no-go' signal along with the target stimulus, telling the subject to withhold a response.…”
mentioning
confidence: 89%
“…While these accounts do not all logically require that the locus of the residual cost is response-selection, that seems to have been the default assumption (e.g., Allport et al, 1994;Meiran, 2000;Waszak et al, 2003;Yeung & Monsell, 2003), and a late locus appears to be intrinsic to the Schuch and Koch (2003) account. We used event-related potentials to localize the effect of a task-switch within the latent interval.…”
Section: Theories Of the (Residual) Task-switch Cost And Its Locusmentioning
confidence: 99%
“…This includes permanent switching between stimulus information, between tasks, and between actions, being particularly demanding when there is high similarity between tasks, for example, because of overlapping stimulus or response categories (Brass et al, 2003;Schuch & Koch, 2003;Meiran, 2000). Switching between two tasks has been associated with activity in the lateral frontal cortex (Braver, Reynolds, & Donaldson, 2003;Brass & von Cramon, 2002;Dove, Pollmann, Schubert, Wiggins, & von Cramon, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the engagement in a new task triggers inhibition of the just-executed task, resulting in increased RTs when one has to switch back to this task after only one intermediate trial (e.g., Arbuthnott & Frank, 2000;Mayr & Keele, 2000). Like N Á1 shift cost, the N Á2 repetition cost was supposed to depend to a large degree on interference resolution in the preceding trial (Schuch & Koch, 2003). However, in contrast to NÁ1 shift cost, it is widely accepted that N Á2 repetition cost results from persisting inhibition of a task that was inhibited during interference resolution in the preceding trial.…”
mentioning
confidence: 99%
“…In task-switching experiments, the difference in reaction time (RT) and error rate between task-repeat and taskswitch trials represents a disadvantage of switching from one task to another, which is usually denoted as (N Á1) shift cost (e.g., Allport, Styles, & Hsieh, 1994;Meiran, 1996;Rogers & Monsell, 1995). It has been suggested that the NÁ1 shift cost depends largely on the resolution of interference in the preceding trial (e.g., Allport & Wylie, 2000;Koch & Philipp, 2005;Schuch & Koch, 2003). However, currently there is a debate whether N Á1 shift cost represents a disadvantage of switching to a task that was inhibited during interference resolution in the preceding trial or an advantage of repeating a task that was activated during interference resolution in the preceding trial (e.g., Dreisbach, Haider, & Kluwe, 2002;Koch & Philipp, 2005;Sohn & Carlson, 2000).…”
mentioning
confidence: 99%